Fitur Transaksi Platform Gojek: Paylater dalam Tinjauan Hukum Islam dan Fatwa No. 116/DSN-MUI/IIX/2017 tentang Uang Elektronik Syariah - Yenni Batubara (El-Mashlahah, 2021)
Lending and borrowing in the millennial era are not limited to face to face. The emergence of FinTech makes it easy for people to transact with various products, one of which is online credit. With online credit, people can shop now and pay later with the PayLater feature. The PayLater feature is widely used by various platforms, one of which is Gojek and its PayLater Gojek. Gojek PayLater provides loans of up to IDR 500,000 / month for users which can be used to transact on the Gojek application only by ordering various services. This feature can be used by Gojek platform users in accordance with the provisions set by Gojek PayLater. So this research aims to determine whether the concept of borrowing and borrowing (qarad) Gojek PayLater is in accordance with the Islamic Syariat, which will be analyzed using the concept of qarad, and Fatwa No. 116 /DSN-MUI/IX/2017 About Sharia Electronic Money. The research method used is an empirical study with a socio-legal research approach, and analyzed by inductive descriptive techniques. Based on the results of the analysis carried out, it can be concluded that the implementation of the Gojek PayLater e-money qaradh contract has met the pillars of qarad, but the qarad requirements in particular have not been fulfilled and the conditions set by Gojek for the use of the PayLater feature are not in accordance with the provisions of the DSN-MUI fatwa.